Neuroserpin Is Strongly Expressed in the Developing and Adult Mouse Neocortex but Its Absence Does Not Perturb Cortical Lamination and Synaptic Proteome - Kement, Dilara; Reumann, Rebecca; Schostak, Katrin; Voß, Hannah; Douceau, Sara; Dottermusch, Matthias; Schweizer, Michaela; Schlüter, Hartmut; Vivien, Denis; Glatzel, Markus; Galliciotti, Giovanna (Frontiers in Neuroanatomy, 2021)
Neuroserpin is a serine protease inhibitor that regulates the activity of tissue-type plasminogen activator (tPA) in the nervous system. Neuroserpin is strongly expressed during nervous system development as well as during adulthood, when it is predominantly found in regions eliciting synaptic plasticity. In the hippocampus, neuroserpin regulates developmental neurogenesis, synaptic maturation and in adult mice it modulates synaptic plasticity and controls cognitive and social behavior. High expression levels of neuroserpin in the neocortex starting from prenatal stage and persisting during adulthood suggest an important role for the serpin in the formation of this brain region and in the maintenance of cortical functions. In order to uncover neuroserpin function in the murine neocortex, in this work we performed a comprehensive investigation of its expression pattern during development and in the adulthood. Moreover, we assessed the role of neuroserpin in cortex formation by comparing cortical lamination and neuronal maturation between neuroserpin-deficient and control mice. Finally, we evaluated a possible regulatory role of neuroserpin at cortical synapses in neuroserpin-deficient mice. We observed that neuroserpin is expressed starting from the beginning of corticogenesis until adulthood throughout the neocortex in several classes of glutamatergic projection neurons and GABA-ergic interneurons. However, in the absence of neuroserpin we did not detect any alteration either in cortical layer formation, or in neuronal soma size and dendritic length. Furthermore, no significant quantitative changes were observed in the proteome of cortical synapses upon neuroserpin deficiency. We conclude that, although strongly expressed in the neocortex, absence of neuroserpin does not lead to gross developmental abnormalities, and does not perturb the composition of the cortical synaptic proteome.